The mediating effect of handgrip strength on the association between sleep duration and basal metabolic rate in middle-aged and older adults: evidence from the China health and retirement longitudinal study - Sun, Xinxiang; Li, Changqing; Ding, Hong; Zhou, Hao; Bai, Ning; Zhao, Xiaojiang (Frontiers in Public Health, 2025)
BackgroundAnomalies in basal metabolic rate (BMR) among middle-aged and older populations can lead to various metabolism-related diseases, presenting a significant global public health challenge. The association and mechanism between sleep duration and BMR remain unclear. This study aimed to investigate the mediating role of handgrip strength in the relationship between sleep duration and BMR.MethodsThe study utilized data from the 2015 China Health and Retirement Longitudinal Study (CHARLS), comprising 10,161 participants aged 45 and older. The mediating effect of handgrip strength on the relationship between sleep duration and BMR was analyzed using linear regression model and bootstrap method.ResultsAfter controlling for confounding variables, a positive correlation was observed between sleep duration and BMR, with standardized regression coefficients (β) of 1.65, 95% confidence interval (CI) ranging from 0.63 to 2.70, and a significance level of p = 0.002. Grip strength was positively correlated with BMR, β was 4.63, 95% CI: 4.34 to 5.91, p < 0.001. Handgrip strength mediates 22.42% of the total effect linking sleep duration to BMR. The mediating effect was 0.37, 95% CI: 0.07–0.67.ConclusionThe study identified significant positive correlations between sleep duration and BMR, as well as handgrip strength and BMR, with handgrip strength mediating the relationship between sleep duration and BMR.